Cultivating Talent Retention through Green HRM: Exploring the Impact of Organizational Pride in Eco-Conscious Enterprises. - Achmad Basofitrah (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
In the context of increasing environmental awareness and intensifying competition for skilled employees, organizations are required to develop human resource strategies that not only support sustainability goals but also strengthen talent retention. This study examines the effect of Green Human Resource Management (Green HRM) on talent retention, with organizational pride as a mediating variable, in the context of PT. Kencana Agro Persada Riau. A quantitative explanatory design was employed, and data were collected from 200 employees using a structured questionnaire based on a five-point Likert scale. The data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability testing, classical assumption tests, multiple linear regression, and path analysis. Hypothesis testing was conducted at a 5% significance level to evaluate both direct and indirect relationships among the variables. The findings indicate that Green HRM has a positive and significant effect on talent retention and also positively and significantly influences organizational pride. In addition, organizational pride has a positive and significant effect on talent retention and mediates the relationship between Green HRM and talent retention. These results suggest that green-oriented HR practices enhance employees’ intention to remain not only through direct organizational support, but also by fostering a sense of pride in belonging to an environmentally responsible company. The study contributes to the literature by clarifying the psychological mechanism linking Green HRM and talent retention in an eco-conscious enterprise context. Practically, the findings imply that organizations should integrate sustainability values into HR practices in a visible and credible manner in order to strengthen employee pride and improve long-term talent retention.